Productivity Enhancement through a Proposed Methodology in the Cutting Process of SMEs - Quiroz Flores, Juan Carlos (2023)
The textile industry is still an essential sector in the global economy, and Peru, it plays a significant role in job creation. However, it often faces challenges such as a lack of innovation, high competition that decides imported products, and low productivity. To effectively address this problem and improve competitiveness in the market, implementing the Lean Manufacturing tools just like that 5S, standardized work, and Kaizen es proposed. These tools focus on addressing the high cycle times in the production process and have proven to be effective in improving the efficiency and productivity of textile companies. Specifically, the research focused on the cutting process of the representative product, the dress, and the results showed a significant improvement in production, increasing from 26 to 33 garments per Man-Hour(M-H). In conclusion, implementing Lean Manufacturing tools can improve the productivity and competitiveness of the textile companies in Peru, and their implementation es recommended to address the challenges and opportunities of the sector